2020
DOI: 10.1177/0956462420956859
|View full text |Cite
|
Sign up to set email alerts
|

Primary syphilis lesion characteristics, serological response and management in HIV-positive and HIV-negative men who have sex with men

Abstract: The characteristics and serological responses of primary syphilis are not completely understood. We aimed to describe the characteristics, the serological responses and presumptive treatment of primary syphilis in HIV-positive and -negative men who have sex with men (MSM). We conducted a retrospective review of microbiological and demographic information from MSM presenting with primary syphilis. There were 111 cases of primary syphilis in MSM, the median age was 46 (IQR = 37–53years) and 40 (36%) were living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In our study, an apparently overall better serological response was found in PLWH; the primary explanation for this is that PLWH are chronically evaluated in our centre with scheduled visits every 6 months. This increases the detection rate of syphilis infection at earlier stages, which is linked to a better serological response [38].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, an apparently overall better serological response was found in PLWH; the primary explanation for this is that PLWH are chronically evaluated in our centre with scheduled visits every 6 months. This increases the detection rate of syphilis infection at earlier stages, which is linked to a better serological response [38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that MSM presenting with genital ulcers of primary syphilis are offered presumptive treatment on 52–71% of occasions, MSM wait up to 14 days for treatment and are more likely to be treated if they have painless genital lesions. 2,4,5 Benzathine penicillin is the first line treatment for syphilis in our centres, and there have been no restriction of access to benzathine. We aimed to find out what the current clinical practice is when experienced sexual health clinicians are faced with MSM presenting with anogenital ulcers.…”
mentioning
confidence: 99%
“…2 The diagnosis of primary syphilis is by dark-field microscopy (DFM), Treponema pallidum polymerase chain reaction (PCR) or serology. 35 Dark-field microscopy requires skilled staff, and its use is diminishing. Sexual health clinicians need to make a complex clinical decision with MSM presenting with genital ulcers at their first attendance; firstly, the causes of genital ulcers are broad (syphilis, herpes and Lymphogranuloma Venereum), and presumptive treatment is based on factors including penicillin allergy and availability of benzathine penicillin.…”
mentioning
confidence: 99%